Negative electrode current collector, method for manufacturing the same, battery cell, battery, and power using device

CN120453386BActive Publication Date: 2026-11-03CONTEMPORARY AMPEREX TECHNOLOGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410175537.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-02-07
Publication Date
2026-11-03
Estimated Expiration
2044-02-07

AI Technical Summary

Technical Problem

Dendrite formation on the negative electrode of a metal battery cell can cause internal short circuits, affecting reliability and cycle performance.

Method used

Laser irradiation of the metal substrate surface causes the metal grains in the heat-affected zone to melt and recrystallize, forming smaller metal grains. By adjusting the laser irradiation parameters, more grain boundary defects are formed, and the surface energy of the metal substrate is rapidly increased. This improves the wettability of metals such as lithium and sodium on the metal substrate surface, as well as the wettability of the electrolyte, thereby reducing the nucleation overpotential of the negative electrode current collector, reducing dendrite formation, and improving the reliability and cycle performance of the battery cell.

Benefits of technology

By adjusting the laser irradiation processing parameters, smaller metal grains are formed on the surface of the metal substrate, increasing grain boundary defects, improving the wettability of metals such as lithium and sodium and the wettability of the electrolyte, reducing the nucleation overpotential of the negative electrode current collector, reducing dendrite formation, and improving the reliability and cycle performance of the battery cell.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120453386B_ABST
    Figure CN120453386B_ABST
Patent Text Reader

Abstract

The application discloses a negative electrode current collector and a preparation method thereof, a battery monomer, a battery and a power utilization device. The preparation method of the negative electrode current collector comprises the following steps: providing a metal base, the metal base being a two-dimensional metal structure or a three-dimensional porous metal structure; and irradiating the metal base with a laser on at least a part of a surface of the metal base, so that metal grains in a laser ablation heat affected zone of the metal base are fused and recrystallized to form metal grains with a smaller size, thereby obtaining the negative electrode current collector. The application can improve the reliability and cycle performance of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to a negative electrode current collector and its preparation method, a battery cell, a battery, and an electrical device. Background Technology

[0002] Compared to ion-ion battery cells, metal battery cells can achieve higher energy densities. However, unlike the anode of ion-ion battery cells, the anode of metal battery cells suffers from a more severe dendrite problem, which hinders their commercialization. Dendrite growth can cause internal short circuits within the battery cell, affecting its reliability and cycle performance. Summary of the Invention

[0003] This application provides a negative electrode current collector and its preparation method, a battery cell, a battery, and an electrical device, which can improve the reliability and cycle performance of the battery.

[0004] In a first aspect, this application provides a method for preparing a negative electrode current collector, comprising the following steps: providing a metal substrate, wherein the metal substrate is a two-dimensional metal structure or a three-dimensional porous metal structure; irradiating at least a portion of the surface of the metal substrate with a laser to melt and recrystallize the metal grains in the laser ablation heat-affected zone of the metal substrate to form smaller metal grains, thereby obtaining a negative electrode current collector.

[0005] This application enables the metal grains in the heat-affected zone of a metal substrate to melt and recrystallize by adjusting the laser irradiation processing parameters, thereby forming smaller metal grains. Furthermore, the reliability and cycle performance of the battery cell using this negative electrode current collector are improved.

[0006] In some embodiments, the laser that generates the laser is a pulsed laser, wherein the laser wavelength of the pulsed laser is 694 nm to 1070 nm, the average power of the laser is 30 W to 90 W, the pulse repetition frequency of the laser is 30 kHz to 90 kHz, and the pulse width of the laser is 20 ns to 120 ns.

[0007] This application utilizes laser irradiation parameters to melt and recrystallize the metal grains in the heat-affected zone, resulting in smaller metal grains. These smaller grains create more grain boundary defects and rapidly increase the surface energy of the metal substrate. This improves the wettability of metals such as lithium and sodium on the substrate surface, as well as the wettability of the electrolyte. Consequently, it reduces the nucleation overpotential of the negative electrode current collector, decreases dendrite formation, and enhances the reliability and cycle performance of the battery cell. Furthermore, laser irradiation activates the surface of the negative electrode current collector, increasing its electrochemical active area and further improving the cycle performance of the battery cell.

[0008] In some embodiments, the pulse energy of the pulsed laser is 1 mJ.

[0009] In some embodiments, the pulsed laser includes one or more of a ruby ​​laser, a fiber laser, a glass laser, and a YAG laser.

[0010] In some embodiments, the laser wavelength of the pulsed laser is 1050 nm to 1070 nm.

[0011] In some embodiments, the laser is executed at a speed of 1000 mm / s to 3500 mm / s.

[0012] In some embodiments, the initial size of the metal grains in the metal substrate is greater than 100 nm; and / or, the size of the metal grains formed by recrystallization of the laser ablation heat-affected zone of the metal substrate is 10 nm to 100 nm.

[0013] In some embodiments, the metal substrate is a two-dimensional metal structure, and the thickness H1 of the two-dimensional metal structure is 5 μm to 12 μm.

[0014] In some embodiments, the metal substrate is a two-dimensional metal structure, which is a two-dimensional copper foil, a two-dimensional copper alloy foil, a two-dimensional nickel foil, or a two-dimensional nickel alloy foil.

[0015] In some embodiments, the metal substrate is a two-dimensional metal structure, and the average power of the laser is 30W to 80W, optionally 40W to 80W. With the average laser power within this range, a larger laser ablation heat-affected zone can be formed on the surface of the two-dimensional metal structure without causing the entire two-dimensional metal structure to melt. Furthermore, the metal grains in the laser ablation heat-affected zone can melt and recrystallize to form smaller metal grains, thereby improving the reliability and cycle performance of the battery cell.

[0016] In some embodiments, the metal substrate is a two-dimensional metal structure, and the laser pulse repetition frequency is 30 kHz to 80 kHz, optionally 40 kHz to 80 kHz. A laser pulse repetition frequency within this range allows for a larger laser ablation heat-affected zone on the surface of the two-dimensional metal structure without causing overall melting. Furthermore, it allows the metal grains in the laser ablation heat-affected zone to melt and recrystallize, forming smaller metal grains, thereby improving the reliability and cycle performance of the battery cell.

[0017] In some embodiments, the metal substrate is a two-dimensional metal structure, and the pulse width of the laser is 40 ns to 120 ns, optionally 60 ns to 120 ns. A laser pulse width within this range allows for a larger laser ablation heat-affected zone on the surface of the two-dimensional metal structure, and also allows the metal grains in the laser ablation heat-affected zone to melt and recrystallize, forming smaller metal grains. This can better improve the reliability and cycle performance of the battery cell.

[0018] In some embodiments, the metal substrate is a two-dimensional metal structure, and the defocusing amount of the laser is -120 μm to 20 μm, optionally -(H1×70%) μm to 0. When the laser defocusing amount is within the above range, the surface of the two-dimensional metal structure can have a larger laser ablation heat-affected zone, and the metal grains in the laser ablation heat-affected zone can be melted and recrystallized to form smaller metal grains, thereby improving the reliability and cycle performance of the battery cell.

[0019] In some embodiments, the metal substrate is a three-dimensional porous metal structure, and the thickness H2 of the three-dimensional porous metal structure is 80 μm to 1000 μm.

[0020] In some embodiments, the metal substrate is a three-dimensional porous metal structure, which is mesh copper, mesh nickel, foamed copper, or foamed nickel.

[0021] In some embodiments, the metal substrate is a three-dimensional porous metal structure, and the average power of the laser is 40W to 90W, optionally 60W to 90W. With the average laser power within this range, a larger laser ablation heat-affected zone can be formed on the surface of the three-dimensional porous metal structure without burning off some of the filaments. Furthermore, the metal grains in the laser ablation heat-affected zone can melt and recrystallize to form smaller metal grains, thereby improving the reliability and cycle performance of the battery cell.

[0022] In some embodiments, the metal substrate is a three-dimensional porous metal structure, and the pulse repetition frequency of the laser is 40 kHz to 90 kHz, optionally 60 kHz to 90 kHz. A laser pulse repetition frequency within this range allows for a larger laser ablation heat-affected zone on the surface of the three-dimensional porous metal structure without burning off some of the filaments. It also allows the metal grains in the laser ablation heat-affected zone to melt and recrystallize, forming smaller metal grains, thereby improving the reliability and cycle performance of the battery cell.

[0023] In some embodiments, the metal substrate is a three-dimensional porous metal structure, and the pulse width of the laser is 40 ns to 120 ns, optionally 60 ns to 120 ns. A laser pulse width within this range allows for a larger laser ablation heat-affected zone on the surface of the three-dimensional porous metal structure. It also allows for the melting and recrystallization of the metal grains within the laser ablation heat-affected zone, forming smaller metal grains, thereby improving the reliability and cycle performance of the battery cell.

[0024] In some embodiments, the metal substrate is a three-dimensional porous metal structure, and the defocusing amount of the laser is from -(H2×100%)μm to 0, optionally from -(H2×70%)μm to -(H2×50%)μm. When the laser defocusing amount is within the above range, the surface of the three-dimensional porous metal structure can have a large laser ablation heat-affected zone, and the metal grains in the laser ablation heat-affected zone can be melted and recrystallized to form smaller metal grains, thereby improving the reliability and cycle performance of the battery cell.

[0025] In some embodiments, the microstructure morphology of the negative electrode current collector surface includes one or more of the following: surface ablation without pores, pits, bowl-shaped holes, through holes, and grooves.

[0026] In some embodiments, before irradiating the metal substrate surface with a laser, the step of cleaning the surface of the metal substrate of oil, impurities and / or oxide layers is further included.

[0027] Secondly, this application provides a negative electrode current collector, which includes a laser ablation heat-affected zone and a non-laser ablation heat-affected zone, wherein the metal grain size of the laser ablation heat-affected zone is smaller than the metal grain size of the non-laser ablation heat-affected zone.

[0028] In some embodiments, the metal grain size of the laser ablation heat-affected zone is 10nm-100nm; and / or, the metal grain size of the non-laser ablation heat-affected zone is greater than 100nm.

[0029] In some embodiments, the microstructure morphology of the negative electrode current collector surface includes one or more of the following: surface ablation without pores, pits, bowl-shaped holes, through holes, and grooves.

[0030] In some embodiments, the negative electrode current collector is prepared by the preparation method of the first aspect of this application.

[0031] Thirdly, this application provides a battery cell, which includes a negative electrode current collector prepared by the preparation method of the first aspect of this application or the negative electrode current collector of the second aspect of this application, wherein the battery cell includes at least one of a negative electrode-free lithium metal battery cell and a negative electrode-free sodium metal battery cell.

[0032] Fourthly, this application provides a battery that includes the battery cell of the third aspect of this application.

[0033] Fifthly, this application provides an electrical device that includes the battery of the fourth aspect of this application, said battery being used to provide electrical energy.

[0034] The electrical device of this application includes the battery provided in this application, and therefore has at least the same advantages as the battery. Attached Figure Description

[0035] To more clearly illustrate the technical solutions of the embodiments of this application, the accompanying drawings used in the embodiments of this application will be briefly described below. Obviously, the drawings described below are only some embodiments of this application. For those skilled in the art, other drawings can be obtained based on the drawings without creative effort.

[0036] Figure 1 The diagram shows a schematic of a battery cell provided in some embodiments of this application.

[0037] Figure 2 An exploded view of a battery cell provided in some embodiments of this application is shown.

[0038] Figure 3 This document shows schematic diagrams of battery modules provided in some embodiments of this application.

[0039] Figure 4 This illustration shows a schematic diagram of a battery pack provided in some embodiments of this application.

[0040] Figure 5 yes Figure 4 The diagram shown is an exploded view of the battery pack.

[0041] Figure 6 The images shown are scanning electron microscope images of negative electrode current collectors provided in some embodiments of this application.

[0042] Figure 7 The following are scanning electron microscope images of negative electrode current collectors provided in other embodiments of this application.

[0043] Figure 8 The images shown are scanning electron microscope images of the negative electrode current collector provided in some other embodiments of this application.

[0044] Figure 9 The images shown are scanning electron microscope images of the negative electrode current collector provided in some other embodiments of this application.

[0045] Figure 10 The images shown are scanning electron microscope images of the negative electrode current collector provided in some other embodiments of this application.

[0046] Figure 11 A schematic diagram of an electrical device provided in some embodiments of this application is shown.

[0047] Figure 12 X-ray diffraction images of the negative electrode current collectors of Comparative Example 1-1 and Examples 1-9 are shown. Curve I represents the X-ray diffraction image of the negative electrode current collector of Comparative Example 1-1, and curve II represents the X-ray diffraction image of the negative electrode current collector of Examples 1-9.

[0048] Figure 13 The electron backscatter diffraction (EBSD) images of the negative electrode current collectors of Comparative Example 1-1 and Examples 1-9 are shown. Figure (a) shows the electron backscatter diffraction (EBSD) image of the negative electrode current collector of Comparative Example 1-1, and Figure (b) shows the electron backscatter diffraction (EBSD) image of the negative electrode current collectors of Examples 1-9.

[0049] The accompanying drawings are not necessarily drawn to scale.

[0050] The reference numerals in the attached diagram are explained as follows: 1 Battery pack, 2 Upper housing, 3 Lower housing, 4 Battery module, 5 Battery cell, 51 Housing, 52 Electrode assembly, 53 Cover plate. Detailed Implementation

[0051] The following detailed description, with appropriate reference to the accompanying drawings, discloses embodiments of the negative electrode current collector and its preparation method, battery cell, battery, and power device of this application. However, unnecessary detailed descriptions may be omitted. For example, detailed descriptions of well-known matters and repetitive descriptions of practically identical structures may be omitted. This is to avoid unnecessarily lengthy descriptions and to facilitate understanding by those skilled in the art. Furthermore, the accompanying drawings and the following description are provided to enable those skilled in the art to fully understand this application and are not intended to limit the subject matter of the claims.

[0052] The "range" disclosed in this application is defined by a lower limit and an upper limit. A given range is defined by selecting a lower limit and an upper limit, which define the boundaries of a particular range. Ranges defined in this way can include or exclude endpoints and can be arbitrarily combined; that is, any lower limit can be combined with any upper limit to form a range. For example, if ranges of 60-120 and 80-110 are listed for a specific parameter, it is expected that ranges of 60-110 and 80-120 are also included. Furthermore, if minimum range values ​​of 1 and 2 are listed, and if maximum range values ​​of 3, 4, and 5 are listed, then the following ranges are all expected: 1-3, 1-4, 1-5, 2-3, 2-4, and 2-5. In this application, unless otherwise stated, the numerical range "ab" represents a shortened representation of any combination of real numbers between a and b, where a and b are real numbers. For example, the numerical range "0-5" indicates that all real numbers between "0-5" have been listed in this article; "0-5" is simply a shortened representation of these numerical combinations. Furthermore, when a parameter is stated as an integer ≥2, it is equivalent to disclosing that the parameter is, for example, an integer such as 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0053] Unless otherwise specified, all embodiments and optional embodiments of this application may be combined with each other to form new technical solutions, and such technical solutions should be considered to be included in the disclosure of this application.

[0054] Unless otherwise specified, all technical features and optional technical features of this application may be combined to form new technical solutions, and such technical solutions shall be deemed to be included in the disclosure of this application.

[0055] Unless otherwise specified, all steps in this application may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or it may include steps (b) and (a) performed sequentially. For example, the method may also include step (c), indicating that step (c) may be added to the method in any order. For example, the method may include steps (a), (b), and (c), or it may include steps (a), (c), and (b), or it may include steps (c), (a), and (b), etc.

[0056] In this application, the terms "multiple" or "various" refer to two or more kinds of things.

[0057] In the description of the embodiments of this application, unless otherwise specified, "above" or "below" the second feature can mean that the first feature is in direct contact with the second feature, or that the first feature is in indirect contact with the second feature through an intermediate medium. Furthermore, "above," "over," and "on top" can mean that the first feature is directly above or diagonally above the second feature, or simply that the first feature is at a higher horizontal level than the second feature. "Below," "below," and "under" the second feature can mean that the first feature is directly below or diagonally below the second feature, or simply that the first feature is at a lower horizontal level than the second feature.

[0058] Unless otherwise stated, the terms used in this application have the common meanings as commonly understood by those skilled in the art.

[0059] Unless otherwise stated, the values ​​of the parameters mentioned in this application can be determined using various testing methods commonly used in the art, for example, according to the testing methods given in the embodiments of this application. Unless otherwise stated, the test temperature for each parameter is 25°C.

[0060] The battery mentioned in the embodiments of this application can be a single physical module comprising one or more battery cells to provide higher voltage and capacity. For example, the battery mentioned in this application can include battery cells, battery modules, or battery packs.

[0061] A battery cell is the smallest unit that makes up a battery, and it can independently perform the functions of charging and discharging. A battery cell can be cylindrical, cuboid, or other shapes, and the embodiments of this application are not limited in this respect. Figure 1 The example shown is a rectangular battery cell 5.

[0062] When there are multiple battery cells, they are connected in series, parallel, or mixed via a busbar. In some embodiments, the battery can be a battery module; when there are multiple battery cells, they are arranged and fixed to form a battery module. In some embodiments, the battery can be a battery pack, which includes a housing and battery cells, with the battery cells or battery modules housed within the housing. In some embodiments, the housing can be part of the vehicle's chassis structure. For example, a portion of the housing can be at least part of the vehicle's floor, or a portion of the housing can be at least part of the vehicle's crossbeams and longitudinal beams.

[0063] In some embodiments, the battery can be an energy storage device. Energy storage devices include energy storage containers, energy storage cabinets, etc.

[0064] The battery cell includes an electrode assembly. The electrode assembly can be a wound structure or a stacked structure, and the embodiments of this application are not limited to this.

[0065] The battery cell may also include an outer packaging, which can be used to encapsulate the electrode assembly. The outer packaging can be a rigid shell, such as a hard plastic shell, aluminum shell, or steel shell. The outer packaging can also be a flexible package, such as a pouch-type flexible package. The material of the flexible package can be plastic, such as one or more of polypropylene (PP), polybutylene terephthalate (PBT), and polybutylene succinate (PBS).

[0066] In some embodiments, such as Figure 2 As shown, the outer packaging may include a housing 51 and a cover 53. The housing 51 may include a base plate and side plates connected to the base plate, the base plate and side plates enclosing a receiving cavity. The housing 51 has an opening communicating with the receiving cavity, and the cover 53 is used to cover the opening to close the receiving cavity. Electrode assemblies 52 are encapsulated in the receiving cavity. The number of electrode assemblies 52 contained in the battery cell 5 may be one or more, and can be adjusted according to requirements.

[0067] In some embodiments, individual battery cells can be assembled into a battery module, and the number of individual battery cells contained in the battery module can be multiple, the specific number of which can be adjusted according to the application and capacity of the battery module. Figure 3 This is a schematic diagram of battery module 4 as an example. Figure 3 As shown, in battery module 4, multiple battery cells 5 can be arranged sequentially along the length of battery module 4. Of course, they can also be arranged in any other manner. Furthermore, these multiple battery cells 5 can be fixed in place using fasteners.

[0068] Optionally, the battery module 4 may also include a housing with a receiving space in which multiple battery cells 5 are received.

[0069] In some embodiments, the battery modules described above can also be assembled into a battery pack, and the number of battery modules contained in the battery pack can be adjusted according to the application and capacity of the battery pack.

[0070] Figure 4 and Figure 5 This is a schematic diagram of battery pack 1 as an example. Figure 4 and Figure 5 As shown, the battery pack 1 may include a housing and multiple battery modules 4 disposed within the housing. The housing includes an upper housing 2 and a lower housing 3. The upper housing 2 covers the lower housing 3, forming a closed space for accommodating the battery modules 4. The multiple battery modules 4 can be arranged in any manner within the housing.

[0071] The battery cells provided in the embodiments of this application may include negative electrode-free lithium metal battery cells, negative electrode-free sodium metal battery cells, etc.

[0072] A negative electrode-free battery cell typically refers to a battery cell in which no negative electrode active material layer is actively formed on the negative electrode side during the battery cell manufacturing process. For example, the negative electrode active material layer is not formed at the negative electrode through coating or deposition processes, or it is formed from a carbonaceous active material layer. During the first charge, ions gain electrons on the negative electrode side and deposit metal on the surface of the negative electrode current collector. During discharge, the metal can be converted back into ions and return to the positive electrode, achieving cyclic charging and discharging. Compared to other battery cells, a negative electrode-free battery cell can achieve a higher energy density due to the absence of a negative electrode active material layer. In some embodiments, to improve battery cell performance, some conventional materials that can be used as negative electrode active materials, such as carbon materials, can also be placed on the negative electrode side of the negative electrode-free battery cell. Although these materials have a certain capacity, because their content is small and they are not used as the main negative electrode active material in the battery cell, such a battery cell can still be considered a negative electrode-free battery cell. The Cell Balance (CB) value of a negative electrode-free battery cell is typically very small; for example, in some embodiments, the CB value of a negative electrode-free battery cell can be less than or equal to 0.1. The CB value is the capacity per unit area of ​​the negative electrode divided by the capacity per unit area of ​​the positive electrode in the battery cell. Because a negative electrode-free battery cell contains little or no negative electrode active material, the capacity per unit area of ​​the negative electrode is small, and therefore the CB value is very small, typically less than or equal to 0.1.

[0073] Copper current collectors are currently the most commonly used current collectors for negative electrodes. Metals such as lithium and sodium have poor wettability on conventional copper current collectors, which leads to a large nucleation overpotential. They tend to preferentially nucleate at certain surface defect sites (such as protrusions and impurities) on conventional copper current collectors. These preferential nucleation sites will form dominant growth points, which can easily lead to dendrite formation and cause internal short circuits in the battery, affecting the battery's reliability and cycle performance.

[0074] This application provides a method for preparing a negative electrode current collector. The negative electrode current collector prepared by this method can be used in negative electrode-free lithium metal batteries and negative electrode-free sodium metal batteries, which can make the battery have good cycle performance and high reliability.

[0075] The method for preparing the negative electrode current collector provided in this application includes the following steps: providing a metal substrate, wherein the metal substrate is a two-dimensional metal structure or a three-dimensional porous metal structure; irradiating at least part of the surface of the metal substrate with a laser to melt and recrystallize the metal grains in the heat-affected zone of the laser ablation of the metal substrate to form smaller metal grains, thereby obtaining the negative electrode current collector.

[0076] Lasers possess high energy; when irradiated onto at least a portion of the surface of a metal substrate, some metal atoms at the irradiated location vaporize and are removed. The metal at the irradiated location that is not ablated and vaporized, along with the surrounding metal, is heated; this area is called the heat-affected zone (HAZ). It is generally believed that laser ablation of the HAZ affects the properties of the metal substrate.

[0077] This application enables the metal grains in the heat-affected zone of a metal substrate to melt and recrystallize by adjusting the laser irradiation processing parameters, thereby forming smaller metal grains. Furthermore, the reliability and cycle performance of the battery cell using this negative electrode current collector are improved.

[0078] By irradiating at least a portion of the surface of a metal substrate with a suitable laser, the metal in the heat-affected zone (HAZ) can be rapidly heated above its melting temperature, followed by rapid melting and recrystallization. This melt-recrystallization process rapidly reduces the size of the metal grains in the HAZ. Smaller grains create more grain boundary defects and rapidly increase the surface energy of the metal substrate. This improves the wettability of metals such as lithium and sodium on the substrate surface, as well as the wettability of the electrolyte. Consequently, it reduces the nucleation overpotential of the negative electrode current collector, decreases dendrite formation, and ultimately improves the reliability and cycle performance of the battery cell. In other words, these smaller metal grains act as an affinity treatment, and their in-situ formation on the metal substrate surface results in better adhesion, further enhancing the cycle performance of the battery cell.

[0079] In addition, laser irradiation can activate the surface of the negative electrode current collector, thereby increasing the electrochemical active area of ​​the negative electrode current collector and further improving the cycle performance of the battery cell.

[0080] In some embodiments, the laser that generates the laser is a pulsed laser, and the laser wavelength of the pulsed laser can be from 694nm to 1070nm, the average power of the laser can be from 30W to 90W, the pulse repetition frequency of the laser can be from 30KHz to 90KHz, and the pulse width of the laser can be from 20ns to 120ns.

[0081] The average power of the laser is 30W to 90W. It can create a large laser ablation heat-affected zone on the surface of the metal substrate without melting the entire metal substrate or burning off some of the filaments. It can also melt and recrystallize the metal grains in the laser ablation heat-affected zone to form smaller metal grains, thereby improving the reliability and cycle performance of the battery cell.

[0082] The laser pulse repetition frequency is 30KHz to 90KHz, which can create a large laser ablation heat-affected zone on the surface of the metal substrate without the entire metal substrate being melted or some of the filaments being burned off. It can also melt and recrystallize the metal grains in the laser ablation heat-affected zone to form smaller metal grains, thereby improving the reliability and cycle performance of the battery cell.

[0083] The large pulse width of the laser widens the heat-affected zone (HAZ) of the metal substrate. A laser pulse width of 20 ns to 120 ns can create a large HAZ on the metal substrate surface, and also allow the metal grains in the HAZ to melt and recrystallize, forming smaller metal grains. This can better improve the reliability and cycle performance of individual battery cells.

[0084] This application utilizes laser irradiation parameters to melt and recrystallize the metal grains in the heat-affected zone, resulting in smaller metal grains. These smaller grains create more grain boundary defects and rapidly increase the surface energy of the metal substrate. This improves the wettability of metals such as lithium and sodium on the substrate surface, as well as the wettability of the electrolyte. Consequently, it reduces the nucleation overpotential of the negative electrode current collector, decreases dendrite formation, and enhances the reliability and cycle performance of the battery cell. Furthermore, laser irradiation activates the surface of the negative electrode current collector, increasing its electrochemical active area and further improving the cycle performance of the battery cell.

[0085] It should be noted that the preparation method that uses laser irradiation with parameters not within the range provided in the embodiments of this application to at least part of the surface of the metal substrate, and can cause the metal grains in the laser ablation heat-affected zone of the metal substrate to melt and recrystallize to form smaller metal grains, i.e., similar concepts with laser irradiation parameters not within the range provided in the embodiments of this application, still falls within the protection scope of this application.

[0086] Optionally, the laser wavelength of the pulsed laser can be from 1050 nm to 1070 nm.

[0087] In some embodiments, the pulse energy of the pulsed laser can be 1 mJ.

[0088] In some embodiments, the pulsed laser may include one or more of a ruby ​​laser, a fiber laser, a glass laser, and a YAG laser. Optionally, the glass laser may be a neodymium glass laser. Optionally, the YAG laser may be a neodymium:YAG laser.

[0089] In some embodiments, the laser actuation speed can be from 1000 mm / s to 3500 mm / s. Changing the laser actuation speed can adjust the microstructure morphology of the negative electrode current collector surface. A slower laser actuation speed results in a closer laser irradiation position, making it easier to form lines; a faster laser actuation speed results in a farther laser irradiation position, making it easier to form holes. An appropriate actuation speed can be selected based on different microstructure morphologies.

[0090] In some embodiments, before laser irradiation treatment, the initial size of the metal grains in the metal substrate can be greater than 100 nm; after laser irradiation treatment, the size of the metal grains formed by recrystallization of the laser ablation heat-affected zone of the metal substrate can be 10 nm-100 nm, and optionally 10 nm-50 nm.

[0091] The size of metal grains can be obtained using electron backscattered diffraction (EBSD) scanning. During testing, the sample is fixed on the sample stage, and parameters such as the angle between the EBSD probe plane and the sample surface to be tested, the accelerating voltage, the magnification, and the step size are adjusted. The number of grains in the observation field is also adjusted, for example, to be greater than or equal to 100. Then, the size of all grains in the analysis area is obtained by scanning the diffraction pattern of the analysis area.

[0092] The metal matrix can be a two-dimensional metal structure or a three-dimensional porous metal structure. The metal matrix can be commercially available or prepared using processes known in the art.

[0093] In some embodiments, the thickness H1 of the two-dimensional metal structure can be from 5 μm to 12 μm, and optionally from 5 μm to 9 μm.

[0094] Alternatively, the two-dimensional metal structure can be a two-dimensional copper foil, a two-dimensional copper alloy foil, a two-dimensional nickel foil, or a two-dimensional nickel alloy foil.

[0095] Optionally, the metal substrate is a two-dimensional metal structure, and the average power of the laser can be from 30W to 80W, for example, 30W, 35W, 40W, 45W, 50W, 55W, 60W, 65W, 70W, 75W, 80W, or any combination of the above values. More preferably, the average power of the laser can be from 40W to 80W.

[0096] When the average power of the laser is within the above range, it can create a large laser ablation heat-affected zone on the surface of the two-dimensional metal structure without causing the entire two-dimensional metal structure to melt. It can also cause the metal grains in the laser ablation heat-affected zone to melt and recrystallize to form smaller metal grains, thereby improving the reliability and cycle performance of the battery cell.

[0097] Optionally, the metal substrate is a two-dimensional metal structure, and the laser pulse repetition frequency can be from 30 kHz to 80 kHz, for example, 30 kHz, 35 kHz, 40 kHz, 45 kHz, 50 kHz, 55 kHz, 60 kHz, 65 kHz, 70 kHz, 75 kHz, 80 kHz, or any range of the above values. More preferably, the laser pulse repetition frequency can be from 40 kHz to 80 kHz.

[0098] With the laser pulse repetition frequency within the above range, a larger laser ablation heat-affected zone can be formed on the surface of the two-dimensional metal structure without the overall melting of the two-dimensional metal structure. Furthermore, the metal grains in the laser ablation heat-affected zone can be melted and recrystallized to form smaller metal grains, thereby improving the reliability and cycle performance of the battery cell.

[0099] Optionally, the metal substrate is a two-dimensional metal structure, and the laser pulse width can be from 40 ns to 120 ns, for example, 40 ns, 45 ns, 50 ns, 55 ns, 60 ns, 65 ns, 70 ns, 75 ns, 80 ns, 90 ns, 100 ns, 110 ns, 120 ns, or any range of the above values. More preferably, the laser pulse width can be from 60 ns to 120 ns.

[0100] When the laser pulse width is within the above range, a larger laser ablation heat-affected zone can be formed on the surface of the two-dimensional metal structure. Furthermore, the metal grains in the laser ablation heat-affected zone can be melted and recrystallized to form smaller metal grains, thereby improving the reliability and cycle performance of the battery cell.

[0101] Optionally, the metal substrate is a two-dimensional metal structure, and the defocusing amount of the laser can be from -120μm to 20μm, optionally from -(H1×100%)μm to 0, and more preferably from -(H1×70%)μm to 0.

[0102] Within the above-mentioned range, the defocusing amount of the laser can create a larger laser ablation heat-affected zone on the surface of the two-dimensional metal structure. It can also cause the metal grains in the laser ablation heat-affected zone to melt and recrystallize to form smaller metal grains, thereby improving the reliability and cycle performance of the battery cell.

[0103] In some embodiments, the thickness H2 of the three-dimensional porous metal structure can be from 80 μm to 1000 μm, and optionally from 100 μm to 600 μm.

[0104] Alternatively, the three-dimensional porous metal structure can be mesh copper, mesh nickel, foamed copper, or foamed nickel.

[0105] Optionally, the metal substrate is a three-dimensional porous metal structure, and the average power of the laser can be from 40W to 90W, for example, 40W, 45W, 50W, 55W, 60W, 65W, 70W, 75W, 80W, 85W, 90W, or any combination of the above values. More preferably, the average power of the laser can be from 60W to 90W.

[0106] When the average power of the laser is within the above range, it can create a large laser ablation heat-affected zone on the surface of the three-dimensional porous metal structure without burning off some of the filaments. It can also cause the metal grains in the laser ablation heat-affected zone to melt and recrystallize to form smaller metal grains, thereby improving the reliability and cycle performance of the battery cell.

[0107] Optionally, the metal substrate is a three-dimensional porous metal structure, and the laser pulse repetition frequency can be from 40 kHz to 90 kHz, for example, 40 kHz, 45 kHz, 50 kHz, 55 kHz, 60 kHz, 65 kHz, 70 kHz, 75 kHz, 80 kHz, 85 kHz, 90 kHz, or any range of the above values. More preferably, the laser pulse repetition frequency can be from 60 kHz to 90 kHz.

[0108] With the laser pulse repetition frequency within the above range, a larger laser ablation heat-affected zone can be formed on the surface of the three-dimensional porous metal structure without burning off some of the filaments. Furthermore, the metal grains in the laser ablation heat-affected zone can be melted and recrystallized to form smaller metal grains, thereby improving the reliability and cycle performance of the battery cell.

[0109] Optionally, the metal substrate is a three-dimensional porous metal structure, and the laser pulse width can be from 40 ns to 120 ns, for example, 40 ns, 45 ns, 50 ns, 55 ns, 60 ns, 65 ns, 70 ns, 75 ns, 80 ns, 90 ns, 100 ns, 110 ns, 120 ns, or any range of the above values. More preferably, the laser pulse width can be from 60 ns to 120 ns.

[0110] When the pulse width of the laser is within the above range, a larger laser ablation heat-affected zone can be formed on the surface of the three-dimensional porous metal structure. Furthermore, the metal grains in the laser ablation heat-affected zone can be melted and recrystallized to form smaller metal grains, thereby improving the reliability and cycle performance of the battery cell.

[0111] Optionally, the metal substrate is a three-dimensional porous metal structure, and the defocusing amount of the laser can be from -(H2×150%)μm to 0, optionally from -(H2×100%)μm to 0, and more preferably from -(H2×70%)μm to -(H2×50%)μm.

[0112] Within the above-mentioned range, the defocusing amount of the laser can create a larger laser ablation heat-affected zone on the surface of the three-dimensional porous metal structure. It can also cause the metal grains in the laser ablation heat-affected zone to melt and recrystallize to form smaller metal grains, thereby improving the reliability and cycle performance of the battery cell.

[0113] In some embodiments, after laser irradiation treatment, the microstructure morphology of the negative electrode current collector surface may include one or more of the following: surface ablation without pores, pits, bowl-shaped holes, through holes, and grooves.

[0114] Optionally, after laser irradiation, the microstructure morphology of the two-dimensional metal structure surface may include one or more of the following: surface ablation without holes, bowl-shaped holes, through holes, and grooves.

[0115] The size of the metal grains in the ablation-free but un-pore-forming areas and their vicinity is reduced, for example, to 10nm-100nm, or optionally 10nm-50nm.

[0116] The size of the metal grains in and around the bowl hole is reduced, for example, to 10nm-100nm, or optionally to 10nm-50nm.

[0117] The size of the metal grains at and around the edge of the via is reduced, for example, to 10nm-100nm, or optionally to 10nm-50nm.

[0118] The size of the metal grains in and around the groove location is reduced, for example, to 10nm-100nm, or optionally to 10nm-50nm.

[0119] Optionally, the bowl holes can be an array of bowl holes.

[0120] Optionally, the aperture of the array bowl can be 20μm-50μm, the aperture spacing can be greater than or equal to 15μm, and the aperture depth can be less than or equal to 2 / 3 of the thickness H1 of the negative electrode current collector. Further, the aperture spacing can be less than 100μm.

[0121] Optionally, the vias can be arrayed vias.

[0122] Optionally, the aperture of the array vias can be 20μm-140μm, and the aperture spacing can be greater than or equal to 15μm. Further, the aperture spacing can be less than 100μm.

[0123] Hole spacing refers to the shortest distance between the edges of two adjacent holes.

[0124] Optionally, the spacing between the grooves can be greater than or equal to 15 μm, and the depth of the grooves can be less than or equal to 2 / 3 of the thickness H1 of the negative electrode current collector.

[0125] like Figure 6 As shown, after laser irradiation, the surface of the two-dimensional metal structure is ablated but no holes are formed.

[0126] Optionally, the area percentage of the region on the surface of the two-dimensional metal structure where metal grains melt and recrystallize after laser irradiation treatment can be 40%-100%, and more preferably 50%-100%, 60%-100%, 70%-100%, or 80%-100%.

[0127] like Figure 7 As shown, after laser irradiation, an array of bowl-shaped holes is formed on the surface of the two-dimensional metal structure.

[0128] like Figure 8 As shown, after laser irradiation, an array of through holes is formed on the surface of the two-dimensional metal structure.

[0129] like Figure 9 As shown, after laser irradiation, grooves were formed on the surface of the two-dimensional metal structure.

[0130] Optionally, after laser irradiation, the microstructure morphology of the three-dimensional porous metal structure surface may include one or more of the following: surface ablation without pores, pits, etc.

[0131] The size of the metal grains in the ablation-free but un-pore-forming areas and their vicinity is reduced, for example, to 10nm-100nm, or optionally 10nm-50nm.

[0132] The size of the metal grains in and around the pit is reduced, for example, to 10nm-100nm, or optionally to 10nm-50nm.

[0133] like Figure 10 As shown, after laser irradiation, the surface of the foam metal structure was ablated but no pores were formed.

[0134] In some embodiments, before irradiating the metal substrate surface with a laser, the step may further include: cleaning the surface of the metal substrate of oil, impurities, and / or oxide layers. Optionally, cleaning may include ultrasonic cleaning or chemical cleaning. Cleaning may include water washing, weak acid washing, or alcohol washing.

[0135] This application also provides a negative electrode current collector. The negative electrode current collector includes a laser ablation heat-affected zone and a non-laser ablation heat-affected zone, wherein the metal grain size of the laser ablation heat-affected zone is smaller than that of the non-laser ablation heat-affected zone.

[0136] The metal grains in the heat-affected zone (HAZ) etched by laser ablation are smaller. These smaller grains create more grain boundary defects and rapidly increase the surface energy of the negative electrode current collector. This improves the wettability of metals such as lithium and sodium on the surface of the negative electrode current collector, as well as the wettability of the electrolyte. Consequently, it reduces the nucleation overpotential of the negative electrode current collector, decreases dendrite formation, and improves the reliability and cycle performance of the battery cell. Simultaneously, the increased electrochemical active area of ​​the negative electrode current collector further enhances the cycle performance of the battery cell.

[0137] The heat-affected zone of laser ablation can be a continuous area or multiple discontinuous areas set at intervals.

[0138] In some embodiments, the non-laser ablation heat-affected zone may include at least a portion of the surface region, that is, at least a portion of the surface of the negative electrode current collector may be a non-laser ablation heat-affected zone.

[0139] In some embodiments, the metal grain size of the laser-ablated heat-affected zone can be 10nm-100nm, and optionally 10nm-50nm.

[0140] In some embodiments, the metal grain size in the non-laser ablation heat-affected zone can be greater than 100 nm.

[0141] In some embodiments, the microstructure morphology of the negative electrode current collector surface includes one or more of the following: surface ablation without pores, pits, bowl-shaped holes, through holes, and grooves.

[0142] The negative electrode current collector has a two-dimensional metal structure or a three-dimensional porous metal structure.

[0143] Optionally, the microstructure morphology of the two-dimensional metal structure surface may include one or more of the following: surface ablation without holes, bowl-shaped holes, through holes, and grooves.

[0144] The size of the metal grains in and around the ablated but un-pored areas is smaller. Optionally, the size of the metal grains in and around the ablated but un-pored areas can be 10 nm-100 nm, or optionally 10 nm-50 nm.

[0145] The size of the metal grains in and around the bowl-shaped opening is smaller. Optionally, the size of the metal grains in and around the bowl-shaped opening can be 10nm-100nm, or optionally 10nm-50nm.

[0146] The size of the metal grains at and around the via edge is smaller. Optionally, the size of the metal grains at and around the via edge can be 10nm-100nm, or optionally 10nm-50nm.

[0147] The size of the metal grains in and around the groove location is smaller. Optionally, the size of the metal grains in and around the groove location can be 10nm-100nm, or optionally 10nm-50nm.

[0148] Optionally, the bowl holes can be an array of bowl holes.

[0149] Optionally, the aperture of the array bowl can be 20μm-50μm, the aperture spacing can be greater than or equal to 15μm, and the aperture depth can be less than or equal to 2 / 3 of the thickness H1 of the negative electrode current collector. Further, the aperture spacing can be less than 100μm.

[0150] Optionally, the vias can be arrayed vias.

[0151] Optionally, the aperture of the array vias can be 20μm-140μm, and the aperture spacing can be greater than or equal to 15μm. Further, the aperture spacing can be less than 100μm.

[0152] Optionally, the spacing between the grooves can be greater than or equal to 15 μm, and the depth of the grooves can be less than or equal to 2 / 3 of the thickness H1 of the negative electrode current collector.

[0153] Optionally, the area ratio of the laser ablation heat-affected zone on the surface of the two-dimensional metal structure can be 40%-100%, and more preferably 50%-100%, 60%-100%, 70%-100%, or 80%-100%.

[0154] Optionally, the microstructure morphology of the three-dimensional porous metal structure surface may include one or more of the following: surface ablation without pores, pits, etc.

[0155] The size of the metal grains in the ablation-free but un-pore-forming areas and their vicinity is reduced, for example, to 10nm-100nm, or optionally 10nm-50nm.

[0156] The size of the metal grains in and around the pit is reduced, for example, to 10nm-100nm, or optionally to 10nm-50nm.

[0157] In some embodiments, the negative electrode current collector can be prepared by the above preparation method.

[0158] Other characteristics of the negative electrode current collector can be found in the preparation method described above, and will not be repeated here.

[0159] The negative electrode current collector provided in this application embodiment can be used in negative electrode-free lithium metal batteries and negative electrode-free sodium metal batteries, which can give the battery good cycle performance and high reliability.

[0160] [Positive electrode plate]

[0161] A single battery cell includes a positive electrode plate.

[0162] In some embodiments, the positive electrode includes a positive current collector and a positive electrode film layer disposed on at least one surface of the positive current collector and comprising a positive electrode active material. For example, the positive current collector has two surfaces opposite each other in its thickness direction, and the positive electrode film layer is disposed on either or both of the two opposite surfaces of the positive current collector.

[0163] In some embodiments, the positive electrode active material includes a material capable of extracting and inserting lithium.

[0164] As examples, positive electrode active materials may include, but are not limited to, one or more of lithium transition metal oxides, metal chalcogenides, lithium-containing phosphates, and their respective modified compounds. Examples of lithium transition metal oxides may include, but are not limited to, one or more of lithium cobalt oxides, lithium nickel oxides, lithium manganese oxides, lithium nickel cobalt oxides, lithium manganese cobalt oxides, lithium nickel manganese oxides, lithium nickel cobalt manganese oxides, lithium nickel cobalt aluminum oxides, lithium titanium oxides, and their respective modified compounds. Lithium transition metal oxides may include, but are not limited to, layered structures and spinel structures. Examples of lithium-containing phosphates may include, but are not limited to, lithium iron phosphate, lithium iron phosphate and carbon composites, lithium manganese phosphate, lithium manganese phosphate and carbon composites, lithium iron manganese phosphate, lithium iron manganese phosphate and carbon composites, and their respective modified compounds.

[0165] In some embodiments, to further improve the energy density of a single battery cell, the positive electrode active material may include materials of the general formula Li. a Ni b Co c M d O e D f One or more of lithium transition metal oxides and their modified compounds. 0.8≤a≤1.2, 0.5≤b<1, 0<c<1, 0<d<1, 1≤e≤2, 0≤f≤1, M may include, but is not limited to, one or more of Ge, Mo, Sn, Mn, Al, Zr, Zn, Cu, Cr, Mg, Fe, V, Ti and B, and D may include, but is not limited to, one or more of N, F, S and Cl.

[0166] In some embodiments, the positive electrode active material may simultaneously comprise lithium transition metal oxide and lithium phosphate. This is advantageous for obtaining a battery that balances high capacity and high reliability.

[0167] As an example, the positive electrode active material may include, but is not limited to, LiCoO2, LiNiO2, LiMnO2, and LiNi 1 / 2 Mn 1 / 2O2, LiMn2O4, Li 4 / 3 Ti5 / 3 O4, LiNi 1 / 2 Mn 1 / 2 O2, LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2(NCM333), LiNi 0.5 Co 0.2 Mn 0.3 O2(NCM523), LiNi 0.6 Co 0.2 Mn 0.2 O2(NCM622), LiNi 0.8 Co 0.1 Mn 0.1 O2(NCM811), LiNi 0.80 Co 0.15 Al 0.05 O2, LiFePO4, LiMnPO4, Li 1.13 Ti 0.57 Fe 0.3 One or more of S2.

[0168] In some embodiments, the positive electrode active material includes a material capable of extracting and inserting sodium. For example, the positive electrode active material may include, but is not limited to, one or more of layered transition metal oxides (including but not limited to P2 type, O3 type, etc.), polyanionic materials (such as phosphates, fluorophosphates, pyrophosphates, sulfates, etc.), and Prussian materials.

[0169] In some embodiments, as an example, the positive electrode active material may include, but is not limited to, NaFeO2, NaCoO2, NaCrO2, NaMnO2, NaNiO2, Na 0.67 MO2 (M includes at least two of Fe, Co, Cr, Mn, Ni, V, Ti, and Mo), NaMO2 (M includes at least two of Fe, Co, Ni, V, Ti, and Mo), NaFePO4, NaMnPO4, NaCoPO4, Na4Fe3(PO4)2O7, Na3V2(PO4)2F3, Na3V2(PO4)3, Prussian blue, Prussian white, and one or more of their respective modified compounds.

[0170] The modified compounds for the above-mentioned positive electrode active materials can be obtained by doping and / or surface coating of the positive electrode active materials.

[0171] In some embodiments, the positive electrode film may optionally include a positive electrode conductive agent. As an example, the positive electrode conductive agent may include, but is not limited to, one or more of superconducting carbon, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0172] In some embodiments, the positive electrode film layer may optionally include a positive electrode binder. As an example, the positive electrode binder may include, but is not limited to, one or more of the following: polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, polyethylene oxide, fluorinated acrylate resins, styrene-butadiene rubber (SBR), water-soluble unsaturated resin SR-1B, waterborne acrylic resins (e.g., polyacrylic acid PAA, polymethacrylic acid PMAA, sodium polyacrylate PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), and carboxymethyl chitosan (CMCS).

[0173] In some embodiments, the positive current collector may be a metal foil or a composite current collector. An example of a metal foil is aluminum foil. The composite current collector may include a polymeric material substrate and a metal material layer formed on at least one surface of the polymeric material substrate. As an example, the metal material may include, but is not limited to, one or more of aluminum, aluminum alloys, nickel, nickel alloys, titanium, titanium alloys, silver, and silver alloys. As an example, the polymeric material substrate may include, but is not limited to, one or more of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), and polyethylene (PE).

[0174] The positive electrode film is typically formed by coating a positive electrode slurry onto a positive electrode current collector, followed by drying and cold pressing. The positive electrode slurry is usually formed by dispersing positive electrode active materials, optional positive electrode conductive agents, optional positive electrode binders, and any other components in a solvent and stirring until homogeneous. The solvent can be N-methylpyrrolidone (NMP), but is not limited to it.

[0175] [Electrolytes]

[0176] A single battery cell includes an electrolyte.

[0177] In some embodiments, the electrolyte is an electrolyte solution, which includes an electrolyte salt and an organic solvent.

[0178] In some embodiments, the electrolyte includes anion, which may include bis(fluorosulfonyl)imide anion (FSI). - ), bis(trifluoromethanesulfonyl)imide anion (TFSI) - ), dioxaborate anion (BOB) - ), difluorooxalate borate anion (DFOB) - ), difluorodioxanol phosphate anion (DFOP) - ), tetrafluorooxalate phosphate anion (TFOP) -), difluorophosphate anion (PO2F2) - ), hexafluorophosphate anion (PF6) - ), tetrafluoroborate anion (BF4) - ), hexafluoroarsenate anion (AsF6) - ), trifluoromethanesulfonate anion (CF3SO3) - One or more of the following.

[0179] In some embodiments, the electrolyte includes cations, which may include one or more of lithium ions and sodium ions.

[0180] In some embodiments, the concentration of the electrolyte salt may be 0.3 mol / L or higher, optionally 0.7 mol / L or higher, and further optionally 4 mol / L or lower, optionally 2.5 mol / L or lower, or 1.7 mol / L or lower. When the concentration of the electrolyte salt is within the above range, the electrolyte can have a suitable ionic conductivity.

[0181] Organic solvents may include, but are not limited to, one or more of esters, ethers, sulfones, and nitriles. Esters may include, but are not limited to, one or more of carbonates, phosphate esters, carboxylic esters, sulfate esters, and sulfonates. Carbonates may include cyclic carbonates and / or chain carbonates; optionally, carbonates may include both cyclic and chain carbonates. Chain carbonates may include low-viscosity polar chain carbonates, aliphatic branched carbonates, etc.

[0182] As an example, organic solvents may include, but are not limited to, ethylene carbonate (EC), propylene carbonate (PC), butene carbonate, ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), sulfolane (SF), dimethyl sulfone (MSM), methyl ethyl sulfone (EMS), diethyl sulfone (ESE), dimethyl ether tetraethylene glycol (TEGDME), ethylene glycol dimethyl ether (DME), 1,3-dioxolane (DOL), trimethyl phosphate, 3-methoxypropionitrile, H(CF2)2OCH3, C4F9O CH3, H(CF2)2OCH2CH3, H(CF2)2OCH2CF3, H(CF2)2CH2O(CF2)2H, CF3CHFCF2OCH3, CF3CHFCF2OCH2CH3, 2-trifluoromethylhexafluoropropyl methyl ether, 2-trifluoromethylhexafluoropropyl ethyl ether, 2-trifluoromethylhexafluoropropyl propyl ether, 3-trifluoromethyloctafluorobutyl methyl ether, 3-trifluoromethyloctafluorobutyl ethyl ether, 3-trifluoromethyloctafluorobutyl propyl ether, 4-trifluoromethyl One or more of the following: decafluoropentyl methyl ether, 4-trifluoromethyl decafluoropentyl ethyl ether, 4-trifluoromethyl decafluoropentyl propyl ether, 5-trifluoromethyl dodecylfluorohexyl methyl ether, 5-trifluoromethyl dodecylfluorohexyl ethyl ether, 5-trifluoromethyl dodecylfluorohexyl propyl ether, 6-trifluoromethyl tetradecafluoroheptyl methyl ether, 6-trifluoromethyl tetradecafluoroheptyl ethyl ether, 6-trifluoromethyl tetradecafluoroheptyl propyl ether, 7-trifluoromethyl hexadecylfluorooctyl methyl ether, 7-trifluoromethyl hexadecylfluorooctyl ethyl ether, and 7-trifluoromethyl hexadecylfluorooctyl propyl ether.

[0183] In some embodiments, the electrolyte may optionally include additives. For example, the additives may include negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery performance, such as additives that improve battery overcharge performance, additives that improve battery high-temperature performance, additives that improve battery low-temperature power performance, etc.

[0184] [Isolation membrane]

[0185] A single battery cell may also include a separator. The separator is located between the positive and negative electrodes and mainly serves to prevent internal short circuits.

[0186] This application does not impose any particular restrictions on the type of separator membrane; any well-known porous metal structure separator membrane with good chemical and mechanical stability can be selected.

[0187] In some embodiments, the material of the separator may include, but is not limited to, one or more of glass fiber, nonwoven fabric, polyethylene, polypropylene, and polyvinylidene fluoride. The separator may be a single-layer film or a multi-layer composite film. When the separator is a multi-layer composite film, the materials of each layer may be the same or different.

[0188] Methods for preparing individual battery cells are well known. In some embodiments, a positive electrode, a separator, a negative current collector, and an electrolyte can be assembled to form a battery cell. As an example, the positive electrode, separator, and negative current collector can be wound and / or stacked to form an electrode assembly. The electrode assembly is then placed in an outer package, dried, and injected with the electrolyte. After vacuum sealing, settling, and formation processes, a battery cell is obtained. Multiple battery cells can be further connected in series, parallel, or a combination thereof to form a battery module. Multiple battery modules can also be connected in series, parallel, or a combination thereof to form a battery pack. In some embodiments, multiple battery cells can also be directly assembled into a battery pack.

[0189] This application also provides an electrical device, which includes the battery provided in this application embodiment. The battery can be used as the power source of the electrical device or as the energy storage unit of the electrical device. The electrical device can be, but is not limited to, mobile devices (such as mobile phones, tablets, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc.

[0190] Electrical devices can choose the type of battery according to their usage needs, such as individual battery cells, battery modules, or battery packs.

[0191] Figure 11 This is a schematic diagram of an example electrical device. The device could be a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. To meet the device's requirements for high power and high energy density, a battery pack or battery module can be used.

[0192] Another example of an electrical device could be a mobile phone, tablet, or laptop. These devices typically require a slim and lightweight design and can use a single battery cell as their power source.

[0193] Example

[0194] The following embodiments describe the disclosure of this application in more detail. These embodiments are merely illustrative, as various modifications and variations will be apparent to those skilled in the art within the scope of the disclosure of this application. Unless otherwise stated, all parts, percentages, and ratios reported in the following embodiments are based on weight, and all reagents used in the embodiments are commercially available or synthesized by conventional methods and can be used directly without further processing, and the instruments used in the embodiments are commercially available.

[0195] Comparative Example 1-1

[0196] A commercially available double-sided two-dimensional optical copper foil with a thickness of 8 μm was first wiped with a 1 mol / L acetic acid solution, then ultrasonically cleaned with ethanol and deionized water, and finally vacuum dried at 80°C to be used as a negative electrode current collector. The initial size of the copper foil metal grains was greater than 100 nm.

[0197] Examples 1-1 to 1-7 and Comparative Examples 1-2 to 1-5

[0198] Commercially available double-sided two-dimensional optical copper foil with a thickness of 8μm was first wiped with a 1mol / L acetic acid solution, then ultrasonically cleaned with ethanol and deionized water, and finally vacuum dried at 80℃.

[0199] The dried copper foil is placed on the workpiece stage and fixed. The laser irradiation treatment parameters are set and the laser beam path is set. The laser is started, the voltage is applied, and the copper foil is irradiated with laser. After the laser irradiation treatment is completed, the sample temperature is lowered to below 30°C, and the sample is taken out as the negative electrode current collector.

[0200] The laser used was a YLPN-1-20X120-100 laser from IPG, with a single laser, a wavelength of 1064 nm, a pulse energy of 1 mJ, an adjustable pulse width ranging from 20 ns to 120 ns, and an adjustable pulse repetition frequency. The laser irradiation parameters are shown in Table 1.

[0201] Before laser irradiation, the initial size of the copper foil metal grains was greater than 100 nm. After laser irradiation, the size of the metal grains formed by recrystallization in the laser ablation heat-affected zone was 10 nm to 100 nm.

[0202] Table 1

[0203]

[0204] Performance testing

[0205] (1) Test on the improvement effect of laser irradiation on copper foil

[0206] After laser irradiation, the metal grains in the area where metal grains melt and recrystallize on the copper foil surface are smaller, and the color of this area will be different from that before laser irradiation. By observing the color change of the copper foil surface after laser irradiation with an optical microscope, the area ratio of the area where metal grains melt and recrystallize on the copper foil surface after laser irradiation can be determined.

[0207] After laser irradiation treatment, the color distinction on the surface of the copper foil is not obvious. It can be assumed that the area of ​​the region where the metal grains melt and recrystallize on the surface of the copper foil after laser irradiation treatment accounts for more than 80% of the total area. At this time, the improvement effect of the copper foil after laser irradiation treatment is excellent.

[0208] After laser irradiation treatment, the area of ​​color change on the copper foil surface accounted for more than 60% and less than 80%, indicating that the improvement effect of laser irradiation treatment on the copper foil was good.

[0209] After laser irradiation treatment, the area of ​​color change on the copper foil surface was greater than or equal to 40% and less than 60%, indicating that the improvement effect of laser irradiation treatment on the copper foil was moderate.

[0210] After laser irradiation treatment, the area of ​​color change on the copper foil surface is greater than or equal to 20% and less than 40%, indicating that the improvement effect of laser irradiation treatment on the copper foil is poor.

[0211] After laser irradiation treatment, the area of ​​color change on the copper foil surface accounted for less than 20%, indicating that the improvement effect of laser irradiation treatment on the copper foil was very poor.

[0212] (2) Nucleation overpotential test

[0213] In an argon-protected glove box, a coin cell was assembled with a lithium metal sheet as the counter electrode and the aforementioned negative electrode current collector. The electrolyte salt was LiFSI at a concentration of 1 mol / L, and the solvent was dimethyl ethylene glycol ether (DME). A 12 μm thick PE membrane was used as the separator.

[0214] After the assembled button cell was left to stand for 12 hours at 25°C, it was tested at 1 mA / cm². 2 Constant current discharge to 1 mAh / cm 2 At the start of the lithium metal deposition process, there is a significant voltage drop followed by a flat voltage plateau. The difference (absolute value) between the voltage at the lowest point of the discharge curve and the flat portion of the voltage plateau is taken as the nucleation overpotential of the negative electrode current collector.

[0215] (3) Cyclic performance test

[0216] Lithium iron phosphate, conductive carbon black (Super P), and binder polyvinylidene fluoride (PVDF) were mixed uniformly in an appropriate amount of solvent N-methylpyrrolidone (NMP) at a weight ratio of 8:1:1 to obtain a positive electrode slurry. The positive electrode slurry was coated onto a positive electrode current collector aluminum foil and dried to obtain a positive electrode sheet. In an argon-protected glove box, the positive electrode sheet and the prepared negative electrode current collector were assembled into a coin cell. The electrolyte salt was LiFSI with a concentration of 1 mol / L, and the solvent was dimethyl glycol ether (DME). A 12 μm thick PE membrane was used as the separator.

[0217] At 25℃, after the assembled coin cells were left to stand for 12 hours, they were charged at a constant current of 0.2C to 3.65V, and then charged at a constant voltage of 3.65V to 0.05C. After the coin cells were left to stand for 10 minutes, they were discharged at a constant current of 0.5C to 2V. The coin cells were then cycled through the above method, and the number of cycles corresponding to 50% of the discharge capacity of the first cycle was recorded. More than six coin cell samples could be used for testing, and the average value of the test results was taken.

[0218] Table 2

[0219]

[0220]

[0221] As shown in Table 2, by selecting appropriate laser irradiation parameters, the metal grains in the heat-affected zone can be melted and recrystallized to form smaller metal grains without the overall melting of the copper foil. This can also improve the cycle performance of the battery.

[0222] The average power of the lasers in Comparative Examples 1-2 was low, and no obvious marks were left on the copper foil surface after laser irradiation, resulting in a lack of significant improvement in battery cycle performance.

[0223] The average power of the lasers in Comparative Examples 1-3 was high, and the copper foil melted after laser irradiation.

[0224] The laser pulse repetition frequency of Comparative Examples 1-4 was low, and no obvious marks were found on the copper foil surface after laser irradiation, resulting in a lack of significant improvement in battery cycle performance.

[0225] The laser pulse repetition frequency of Comparative Examples 1-5 is high, and the copper foil has melted after laser irradiation.

[0226] As can be seen from the test results of Examples 1-1 and 1-2, by further selecting a suitable average laser power, a larger laser ablation heat-affected zone can be formed on the surface of the metal substrate without the overall melting of the metal substrate. Furthermore, the metal grains in the laser ablation heat-affected zone can be melted and recrystallized to form smaller metal grains, thereby improving the cycle performance of the battery.

[0227] As can be seen from the test results of Examples 1-1 and 1-3, by further selecting a suitable laser pulse repetition frequency, a larger laser ablation heat-affected zone can be formed on the surface of the metal substrate without the overall melting of the metal substrate. Furthermore, the metal grains in the laser ablation heat-affected zone can be melted and recrystallized to form smaller metal grains, thereby improving the cycle performance of the battery.

[0228] As can be seen from the test results of Examples 1-1, 1-4 and 1-5, by further selecting an appropriate laser pulse width, a larger laser ablation heat-affected zone can be formed on the surface of the metal substrate. Furthermore, the metal grains in the laser ablation heat-affected zone can be melted and recrystallized to form smaller metal grains, thereby improving the cycle performance of the battery.

[0229] The test results of Examples 1-1, 1-6 and 1-7 show that by further selecting an appropriate laser defocusing amount, the surface of the metal substrate can have a larger laser ablation heat-affected zone, and the metal grains in the laser ablation heat-affected zone can be melted and recrystallized to form smaller metal grains, thereby improving the cycle performance of the battery.

[0230] Examples 1-8 to 1-10

[0231] Commercially available double-sided two-dimensional optical copper foil with a thickness of 8μm was first wiped with a 1mol / L acetic acid solution, then ultrasonically cleaned with ethanol and deionized water, and finally vacuum dried at 80℃.

[0232] The dried copper foil is placed on the workpiece stage and fixed. The laser irradiation treatment parameters are set, and different laser beam paths are set. The laser is started, the voltage is applied, and the copper foil is laser irradiated. After the laser irradiation treatment is completed, the sample temperature is lowered to below 30°C, and the sample is taken out as the negative electrode current collector.

[0233] The laser used was a single YLPN-1-20X120-100 laser from IPG, with a wavelength of 1064 nm, a pulse energy of 1 mJ, an adjustable pulse width ranging from 20 ns to 120 ns, and an adjustable pulse repetition frequency. The laser irradiation parameters are shown in Table 3. The test results are shown in Table 4.

[0234] Before laser irradiation, the initial size of the copper foil metal grains was greater than 100 nm. After laser irradiation, the size of the metal grains formed by recrystallization in the laser ablation heat-affected zone was 10 nm to 100 nm.

[0235] Table 3

[0236]

[0237] Table 4

[0238]

[0239] Figure 12 X-ray diffraction images of the negative electrode current collectors of Comparative Example 1-1 and Examples 1-9 are shown. Curve I represents the X-ray diffraction image of the negative electrode current collector of Comparative Example 1-1, and curve II represents the X-ray diffraction image of the negative electrode current collector of Examples 1-9. Figure 13 The electron backscattering diffraction (EBSD) images of the negative electrode current collectors of Comparative Example 1-1 and Examples 1-9 are shown. Figure (a) shows the electron backscattering diffraction (EBSD) image of the negative electrode current collector of Comparative Example 1-1, and Figure (b) shows the electron backscattering diffraction (EBSD) image of the negative electrode current collectors of Examples 1-9. Figure 12 It can be seen that after laser irradiation, the full width at half maximum (FWHM) of the diffraction peaks of copper increases, indicating that the copper grain size has decreased. Figure 13 It can be seen that after laser irradiation, the laser ablation heat-affected zone formed smaller metal grains, and the laser ablation heat-affected zone was located at the edge of the through hole and its vicinity.

[0240] The test results from Examples 1-1, 1-8 to 1-10 show that when the microstructure morphology of the copper foil surface is bowl-shaped and through-shaped, the battery can have better cycle performance. This is because when the microstructure morphology of the copper foil surface is bowl-shaped and through-shaped, the specific surface area of ​​the copper foil is larger and the electrochemical active area is also larger.

[0241] Comparative Example 2-1

[0242] Commercially available three-dimensional copper foam, 120 μm thick, was first wiped with a 1 mol / L acetic acid solution, then ultrasonically cleaned with ethanol and deionized water, and finally vacuum dried at 80 °C to be used as the negative electrode current collector. The initial size of the copper foam grains was greater than 100 nm.

[0243] Examples 2-1 to 2-8 and Comparative Examples 2-2 to 2-5

[0244] Commercially available 3D foamed copper with a thickness of 120μm was first wiped with a 1mol / L acetic acid solution, then ultrasonically cleaned with ethanol and deionized water, and finally vacuum dried at 80℃.

[0245] The dried copper foam is placed on the workpiece stage and fixed. The laser irradiation treatment parameters are set and the laser beam path is set. The laser is started, the voltage is applied, and the copper foam is irradiated with laser. After the laser irradiation treatment is completed, the sample temperature is lowered to below 30°C, and the sample is taken out as the negative electrode current collector.

[0246] The laser used was a single YLPN-1-20X120-100 laser from IPG, with a wavelength of 1064 nm, a pulse energy of 1 mJ, an adjustable pulse width ranging from 20 ns to 120 ns, and an adjustable pulse repetition frequency. The laser irradiation parameters are shown in Table 5. The test results are shown in Table 6.

[0247] Before laser irradiation, the initial size of the copper foam grains was greater than 100 nm. After laser irradiation, the size of the recrystallized metal grains formed in the laser ablation heat-affected zone was 10 nm to 100 nm.

[0248] Table 5

[0249]

[0250] Table 6

[0251]

[0252]

[0253] As shown in Table 6, by selecting appropriate laser irradiation parameters, the metal grains in the heat-affected zone can be melted and recrystallized to form smaller metal grains without burning off the foamed copper wires. This can improve the cycle performance of the battery.

[0254] In Comparative Example 2-2, the average power of the laser was low, and no obvious traces were left on the surface of the copper foam after laser irradiation, resulting in a lack of significant improvement in battery cycle performance.

[0255] The lasers in Comparative Examples 2 and 3 have a higher average power, and after laser irradiation, the ribs of the foamed copper are burned off.

[0256] The laser pulse repetition frequency of Comparative Examples 2-4 was low, and no obvious traces were left on the surface of the foamed copper after laser irradiation, resulting in an insignificant improvement in battery cycle performance.

[0257] The laser pulse repetition frequency of Comparative Example 2-5 is high, and after laser irradiation, the ribs of the foam copper part are burned off.

[0258] As can be seen from the test results of Examples 2-1 and 2-3, by further selecting a suitable average laser power, more rib surfaces can have laser ablation heat-affected zones without burning off the foamed copper ribs. Furthermore, the metal grains in the laser ablation heat-affected zones can be melted and recrystallized to form smaller metal grains, thereby improving the cycle performance of the battery.

[0259] As can be seen from the test results of Examples 2-1 and 2-4, by further selecting a suitable laser pulse repetition frequency, more rib surfaces can have laser ablation heat-affected zones without burning off the foamed copper ribs. Furthermore, the metal grains in the laser ablation heat-affected zones can be melted and recrystallized to form smaller metal grains, thereby improving the cycle performance of the battery.

[0260] The test results of Examples 2-1, 2-5 and 2-6 show that by further selecting a suitable laser pulse width, more prism surfaces can have laser ablation heat-affected zones, and the metal grains in the laser ablation heat-affected zones can be melted and recrystallized to form smaller metal grains, thereby improving the cycle performance of the battery.

[0261] The test results of Examples 2-1, 2-7 and 2-8 show that by further selecting an appropriate laser defocusing amount, more prism surfaces can have laser ablation heat-affected zones, and the metal grains in the laser ablation heat-affected zones can be melted and recrystallized to form smaller metal grains, thereby improving the cycle performance of the battery.

[0262] The test results from Examples 2-1 and 2-2 show that the formation of pits on the surface of copper foam can improve the cycle performance of the battery. This is because when pits are formed on the surface of copper foam, the specific surface area and electrochemical active area of ​​the copper foam are larger.

[0263] It should be noted that this application is not limited to the above-described embodiments. The above embodiments are merely examples, and any embodiments with the same structure and effect as the technical concept within the scope of this application are included in the technical scope of this application. Furthermore, various modifications that can be conceived by those skilled in the art to the embodiments, and other ways of constructing by combining some of the constituent elements of the embodiments, without departing from the spirit of this application, are also included in the scope of this application.

Claims

1. A method for preparing a negative electrode current collector, characterized in that, Includes the following steps: A metal matrix is ​​provided, wherein the metal matrix is ​​a two-dimensional metal structure or a three-dimensional porous metal structure; At least a portion of the surface of the metal substrate is irradiated with a laser, causing the metal grains in the laser-ablated heat-affected zone of the metal substrate to melt and recrystallize, forming smaller metal grains, thereby obtaining a negative electrode current collector.

2. The preparation method according to claim 1, characterized in that, The laser that generates the laser is a pulsed laser, the laser wavelength of which is 694nm to 1070nm, the average power of which is 30W to 90W, the pulse repetition frequency of which is 30KHz to 90KHz, and the pulse width of which is 20ns to 120ns.

3. The preparation method according to claim 2, characterized in that, The pulse energy of the pulsed laser is 1 mJ.

4. The preparation method according to claim 2, characterized in that, The pulsed laser includes one or more of the following: ruby ​​laser, fiber laser, glass laser, and YAG laser.

5. The preparation method according to claim 2, characterized in that, The pulsed laser has a wavelength of 1050 nm to 1070 nm.

6. The preparation method according to claim 2, characterized in that, The laser's actuation speed is from 1000 mm / s to 3500 mm / s.

7. The preparation method according to claim 2, characterized in that, The initial size of the metal grains in the metal matrix is ​​greater than 100 nm; and / or, The size of the metal grains formed by recrystallization of the laser ablation heat-affected zone of the metal matrix is ​​10nm-100nm.

8. The preparation method according to claim 2, characterized in that, The metal substrate is a two-dimensional metal structure, and the thickness H1 of the two-dimensional metal structure is 5 μm to 12 μm.

9. The preparation method according to claim 8, characterized in that, The two-dimensional metal structure is a two-dimensional copper foil, a two-dimensional copper alloy foil, a two-dimensional nickel foil, or a two-dimensional nickel alloy foil.

10. The preparation method according to any one of claims 8-9, characterized in that, The laser has an average power of 30W to 80W; and / or, The pulse repetition frequency of the laser is 30 kHz to 80 kHz; and / or, The pulse width of the laser is 40 ns to 120 ns; and / or, The defocusing of the laser is from -120μm to 20μm.

11. The preparation method according to claim 10, characterized in that, The laser has an average power of 40W to 80W; and / or, The pulse repetition frequency of the laser is 40 kHz to 80 kHz; and / or, The pulse width of the laser is 60 ns to 120 ns; and / or, The defocusing amount of the laser is from -(H1×70%)μm to 0.

12. The preparation method according to claim 2, characterized in that, The metal substrate is a three-dimensional porous metal structure, and the thickness H2 of the three-dimensional porous metal structure is 80 μm to 1000 μm.

13. The preparation method according to claim 12, characterized in that, The three-dimensional porous metal structure is mesh copper, mesh nickel, foamed copper, or foamed nickel.

14. The preparation method according to any one of claims 12-13, characterized in that, The laser has an average power of 40W to 90W; and / or, The pulse repetition frequency of the laser is 40 kHz to 90 kHz; and / or, The pulse width of the laser is 40 ns to 120 ns; and / or, The defocusing amount of the laser is from -(H2×100%)μm to 0.

15. The preparation method according to claim 14, characterized in that, The laser has an average power of 60W to 90W; and / or, The pulse repetition frequency of the laser is 60 kHz to 90 kHz; and / or, The pulse width of the laser is 60 ns to 120 ns; and / or, The defocusing amount of the laser is from -(H2×70%)μm to -(H2×50%)μm.

16. The preparation method according to claim 1, characterized in that, The microstructure morphology of the negative electrode current collector surface includes one or more of the following: surface ablation without pores, pits, bowl-shaped holes, through holes, and grooves.

17. The preparation method according to claim 1, characterized in that, Before irradiating the surface of the metal substrate with a laser, the method further includes the step of cleaning the surface of the metal substrate of oil, impurities and / or oxide layers.

18. A negative electrode current collector, characterized in that, The negative electrode current collector includes a laser ablation heat-affected zone and a non-laser ablation heat-affected zone, wherein the metal grain size of the laser ablation heat-affected zone is smaller than that of the non-laser ablation heat-affected zone.

19. The negative electrode current collector according to claim 18, characterized in that, The metal grain size of the laser ablation heat-affected zone is 10nm-100nm; and / or, the metal grain size of the non-laser ablation heat-affected zone is greater than 100nm.

20. The negative electrode current collector according to any one of claims 18-19, characterized in that, The microstructure morphology of the negative electrode current collector surface includes one or more of the following: surface ablation without pores, pits, bowl-shaped holes, through holes, and grooves.

21. The negative electrode current collector according to claim 18, characterized in that, It is prepared by the preparation method according to any one of claims 1-17.

22. A single battery cell, characterized in that, The negative electrode current collector is prepared by the preparation method according to any one of claims 1-17 or the negative electrode current collector according to any one of claims 18-21, wherein the battery cell includes at least one of a negative electrode-free lithium metal battery cell and a negative electrode-free sodium metal battery cell.

23. A battery, characterized in that, Includes the battery cell as described in claim 22.

24. An electrical appliance, characterized in that, Includes the battery of claim 23, the battery being used to provide electrical energy.

Citation Information

Patent Citations

  • Preparation method of copper-based current collector of anode-free lithium ion battery

    CN115275212A

  • Process for forming interconnect in semiconductor device

    KR1019980057109A